Enhancing 2SLGBTQIA+ Student Support Through Practical Professional Development and Structured GSA Programming. - Lapointe, Alicia (Canadian Journal of Community Mental Health, 2023)
This article explores how school staff may enhance their capacity to support and affirm 2SLGBTQIA+ youth by meaningfully participating in hands-on professional development and implementing structured mental health promotion and healthy relationships programming in gender and sexuality alliances or other educational venues.